Linguistic measures of personality in group discussions - Spitzley, Lee A.; Wang, Xinran; Chen, Xunyu; Burgoon, Judee K.; Dunbar, Norah E.; Ge, Saiying (Frontiers in Psychology, 2022)
In this study, we examine the relationship between five-factor personality measures and language from 340 participants in a group communication experiment. We introduce several measures of language that are derived from linguistic syntax, in addition to measures identified in prior work. We also investigate linguistic style dynamics over the course of an interaction. After controlling situational and cultural factors, we find predictors of extraversion and agreeableness, but overall fewer significant associations than prior studies. We also find that extraverts maintain greater linguistic style consistency over an interaction. The paper also includes a discussion of the potential for Type I error when studying the relationship between language and personality.